Species Diversity of Dipterocarpaceae in Production Forest of Siberut Island, West Sumatra - Hilwan, Iwan (Proceeding International Conference on Global Resource Conservation, 2013)
Production forest in Sumatra, Kalimantan, and other islands, are located in lowland tropical rain forest, where in that forest type were dominated by plant species of Dipterocarpaceae. Many tree species of Dipterocarpaceae was cut to produce major commercial timber. That timber harvesting activity with selective cutting method can rise impact to stand density and species diversity of Dipterocarpaceae. Because that condition, study on species diversity and stand density of Dipterocarpaceae in virgin forest (VF) and logged over area (LOA) is very important to provide data and information for forest management. According vegetation analysis in 1 ha sample plots at virgin forest and logged over area, can be found 6 species of Dipterocarpaceae, that is 3 species Shorea, 2 species Dipterocarpus, and 1 species Hopea, they are namely: Shorea retinodes v. Slooten, Shorea ovalis (Korth.) Blume, Shorea pauciflora King, Dipterocarpus hasseltii Blume, Dipterocarpus elongatus Korth., dan Hopea dryobalanoides Miq.. Plant species of Dipterocarpaceae especially Shorea pauciflora King, Dipterocarpus elongatus Korth., and Dipterocarpus hasseltii Blume are grown in great number and dominated stand structure of production forest both in virgin forest and logged over forest, whereas in fact these species are cut in timber harvested operation (over 90% of timber cutting). Keywords: Dipterocarpaceae, production forest, selective cutting